Nursing management of the enteral nutrition for a patient with endotracheal intubation for acute respiratory failure complicated with severe pneumonia (1例急性呼吸衰竭气管插管合并重症肺炎患者肠内营养的护理体会) - WANG Jingjing (王晶晶); (周洁); MA Hailian (马海莲); LI Na (李娜); QIAO Xinli (乔新立); MA Shanshan (马珊珊); TANG Ling (唐玲); ZHANG Tingting (张婷婷) (Association of Integrative Nursing, 2023)
This paper summarized the nursing management of the nasogastric enteral nutrition for a patient with endotracheal intubation for acute respiratory failure complicated with severe pneumonia. Nursing interventions such as endotracheal intubation, nursing of enteral nutrition and prevention of aspiration and other issues were carried out to control infection, improve the patient's pneumonia situation and reduce the occurrence of complications. (本文总结1例急性呼吸衰竭气管插管合并重症肺炎患者鼻饲肠内营养液的护理干预措施, 主要从气管插管、肠内营养的护理以及预防误吸等方面进行干预, 旨在控制感染, 改善患者肺炎症状, 减少并发症的发生。)